Consumption with Large Sip Sizes Increases Food Intake and Leads to Underestimation of the Amount Consumed - Bolhuis, Dieuwerke P.; Lakemond, Catriona M. M.; de Wijk, Rene A.; Luning, Pieternel A.; de Graaf, Cees (PLOS ONE, 2013)
Background A number of studies have shown that bite and sip sizes influence the amount of food intake. Consuming with small sips instead of large sips means relatively more sips for the same amount of food to be consumed; people may believe that intake is higher which leads to faster satiation. This effect may be disturbed when people are distracted. Objective The objective of the study is to assess the effects of sip size in a focused state and a distracted state on ad libitum intake and on the estimated amount consumed. Design In this 3×2 cross-over design, 53 healthy subjects consumed ad libitum soup with small sips (5 g, 60 g/min), large sips (15 g, 60 g/min), and free sips (where sip size was determined by subjects themselves), in both a distracted and focused state. Sips were administered via a pump. There were no visual cues toward consumption. Subjects then estimated how much they had consumed by filling soup in soup bowls. Results Intake in the small-sip condition was ∼30% lower than in both the large-sip and free-sip conditions (P<0.001). In addition, subjects underestimated how much they had consumed in the large-sip and free-sip conditions (P<0.03). Distraction led to a general increase in food intake (P = 0.003), independent of sip size. Distraction did not influence sip size or estimations. Conclusions Consumption with large sips led to higher food intake, as expected. Large sips, that were either fixed or chosen by subjects themselves led to underestimations of the amount consumed. This may be a risk factor for over-consumption. Reducing sip or bite sizes may successfully lower food intake, even in a distracted state.